2012
DOI: 10.1007/s00464-012-2388-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired postoperative EGJ relaxation as a determinant of post laparoscopic fundoplication dysphagia: a study with high-resolution manometry before and after surgery

Abstract: FP establishes an efficient antireflux mechanism by correcting hiatal hernia and increasing EGJ pressures. EGJ relaxation as measured by IRP is significantly altered after surgery, leading to more frequent motility disorders, and bolus pressurization. Postoperative dysphagia was associated with higher values of IRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 32 publications
7
30
0
Order By: Relevance
“…[1][2][3] Scheffer et al 5 found increased intra-bolus pressure (IBP) and increased esophagogastric junction (EGJ) relaxation pressure in patients after fundoplication. Recent studies conducted by Marjoux et al 6 included pre-and post-operative analysis of Chicago classification parameters which showed mainly EGJ resting pressure improvement with frequent EGJ relaxation impairment leading to simultaneous motility disorders in post-fundoplication patients. Effective esophageal motility determines esophageal clearance, which is of particular significance for patients with GERD qualified for antireflux surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Scheffer et al 5 found increased intra-bolus pressure (IBP) and increased esophagogastric junction (EGJ) relaxation pressure in patients after fundoplication. Recent studies conducted by Marjoux et al 6 included pre-and post-operative analysis of Chicago classification parameters which showed mainly EGJ resting pressure improvement with frequent EGJ relaxation impairment leading to simultaneous motility disorders in post-fundoplication patients. Effective esophageal motility determines esophageal clearance, which is of particular significance for patients with GERD qualified for antireflux surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Fundoplication is the "gold standard" for GERD treatment as an alternative to pharmacological therapy in PPI non-responders, or when PPI long term therapy is not suitable. 5,6,9 By re-establishing successful EGJ resting pressure and hiatal hernia repair, fundoplication eliminates mechanical factors responsible for reflux events, providing effective and long-term heartburn control in 90% of the patients. Fundoplication not only enhances the EGJ barrier but also alters esophageal motility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Additional problems such as diarrhea and gas-bloating have been reported. 9,27,28 Due to the risks of postoperative complications, many patients dissatisfied with PPI therapy are reluctant to undergo this procedure. Several alternative options for the treatment of GERD have been introduced during the last 2 decades.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 18 patients have completed 3-month follow-up and 14 patients 6-month follow-up. Interim results showed a positive ef- fect on symptoms: GERD-HRQL median (IQR) score was 4 (2-11) at 3 months and 5 (4-9) at 6 months, respectively with P < 0.001 and P < 0.01 when compared to baseline score off PPI (31 [25][26][27][28][29][30][31][32][33][34][35][36][37]). Furthermore, acid exposure time decreased from 11.3% (9.0-15.5%) at baseline to 3.3% (2.5-9.1%) at 3 months and to 2.6% (1.8-5.4%) at 6 months (Fig.…”
mentioning
confidence: 99%